2017
DOI: 10.2196/jmir.3100
|View full text |Cite
|
Sign up to set email alerts
|

eHealth Literacy and Health Behaviors Affecting Modern College Students: A Pilot Study of Issues Identified by the American College Health Association

Abstract: BackgroundThe eHealth Literacy Scale (eHEALS) has been widely adopted by researchers to understand how eHealth literacy can be put into context. eHealth researchers need to know how to promote positive health behavior changes across college students, given the importance of the Internet to acquire and use health information. The American College Health Association identified a set of key health issues that affect college students today. By understanding how eHEALS might be related to college students’ maintena… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
92
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(105 citation statements)
references
References 32 publications
9
92
3
1
Order By: Relevance
“…In this study, our findings illustrate that higher scores of health literacy and digital healthy diet literacy were positively associated with healthier eating behavior during the pandemic for both nursing and medical students. College students with higher eHealth literacy engaged better in positive health-promoting behaviors [ 29 , 55 ]. A previous study also showed that higher e-HDL scores were associated with better health status and health-related behaviors in the general population in Taiwan [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, our findings illustrate that higher scores of health literacy and digital healthy diet literacy were positively associated with healthier eating behavior during the pandemic for both nursing and medical students. College students with higher eHealth literacy engaged better in positive health-promoting behaviors [ 29 , 55 ]. A previous study also showed that higher e-HDL scores were associated with better health status and health-related behaviors in the general population in Taiwan [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that people with higher eHealth literacy have healthier lifestyles than those with lower eHealth literacy in the general population [ 18 ]. Regarding university students, only a few studies have reported on the association between eHealth literacy and lifestyle behaviors, such as regular exercise, healthy eating, and regular sleep, in Taiwan, Greece, and the United States [ 20 , 22 , 27 ]. However, the numbers of participants in these studies [ 20 , 22 , 27 ] were relatively small.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding university students, only a few studies have reported on the association between eHealth literacy and lifestyle behaviors, such as regular exercise, healthy eating, and regular sleep, in Taiwan, Greece, and the United States [ 20 , 22 , 27 ]. However, the numbers of participants in these studies [ 20 , 22 , 27 ] were relatively small. Furthermore, the influence of eHealth literacy on lifestyle behavior may vary depending on the country, cultural background, and degree of internet use [ 17 , 19 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Today's culture enhances patients and healthy individuals to play an active role in taking care of their health. Most young adults are able to search electronic sources for health information and to use these for decision making (Stellefson et al, 2011;Stellefeson et al, 2012;Britt et al, 2017;Bakarman, 2017), and internet is becoming a major source of health information for the new generation (Tao, 2017). Several studies examined students' online habits and their use of internet as a source for health information (Osei Asibey, Agyemang, & Boakye Dankwah, 2017;Albarrak et al, 2016;O'Carroll, 2015;Aldebasi & Ahmed, 2013;Schwartz, 2016;Horgan & Sweeney, 2012;Percheski, 2011;Bensley et al, 2014).…”
Section: Introductionmentioning
confidence: 99%